De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

De novo variants in SNAP25 cause an early-onset developmental and epileptic encephalopathy. - Klöckner, Chiara; Sticht, Heinrich; Zacher, Pia; Popp, Bernt; Babcock, Holly E; Bakker, Dewi P; Barwick, Katy; Bonfert, Michaela V; Bönnemann, Carsten G; Brilstra, Eva H; Chung, Wendy K; Clarke, Angus J; et al. (Genet Med, 2021)
PURPOSE: This study aims to provide a comprehensive description of the phenotypic and genotypic spectrum of SNAP25 developmental and epileptic encephalopathy (SNAP25-DEE) by reviewing newly identified and previously reported individuals. METHODS: Individuals harboring heterozygous missense or loss-of-function variants in SNAP25 were assembled through collaboration with international colleagues, matchmaking platforms, and literature review. For each individual, detailed phenotyping, classification, and structural modeling of the identified variant were performed. RESULTS: The cohort comprises 23 individuals with pathogenic or likely pathogenic de novo variants in SNAP25. Intellectual disability and early-onset epilepsy were identified as the core symptoms of SNAP25-DEE, with recurrent findings of movement disorders, cerebral visual impairment, and brain atrophy. Structural modeling for all variants predicted possible functional defects concerning SNAP25 or impaired interaction with other components of the SNARE complex. CONCLUSION: We provide a comprehensive description of SNAP25-DEE with intellectual disability and early-onset epilepsy mostly occurring before the age of two years. These core symptoms and additional recurrent phenotypes show an overlap to genes encoding other components or associated proteins of the SNARE complex such as STX1B, STXBP1, or VAMP2. Thus, these findings advance the concept of a group of neurodevelopmental disorders that may be termed "SNAREopathies."
Keywords: Brain Diseases; Child, Preschool; Epilepsy; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype; Synaptosomal-Associated Protein 25

De novo variants in TCF7L2 are associated with a syndromic neurodevelopmental disorder. - Dias, Caroline; Pfundt, Rolph; Kleefstra, Tjitske; Shuurs-Hoeijmakers, Janneke; Boon, Elles M J; van Hagen, Johanna M; Zwijnenburg, Petra; Weiss, Marjan M; Keren, Boris; Mignot, Cyril; Isapof, Arnaud; Weiss, Karin; et al. (Am J Med Genet A, 2021)
TCF7L2 encodes transcription factor 7-like 2 (OMIM 602228), a key mediator of the evolutionary conserved canonical Wnt signaling pathway. Although several large-scale sequencing studies have implicated TCF7L2 in intellectual disability and autism, both the genetic mechanism and clinical phenotype have remained incompletely characterized. We present here a comprehensive genetic and phenotypic description of 11 individuals who have been identified to carry de novo variants in TCF7L2, both truncating and missense. Missense variation is clustered in or near a high mobility group box domain, involving this region in these variants' pathogenicity. All affected individuals present with developmental delays in childhood, but most ultimately achieved normal intelligence or had only mild intellectual disability. Myopia was present in approximately half of the individuals, and some individuals also possessed dysmorphic craniofacial features, orthopedic abnormalities, or neuropsychiatric comorbidities including autism and attention-deficit/hyperactivity disorder (ADHD). We thus present an initial clinical and genotypic spectrum associated with variation in TCF7L2, which will be important in informing both medical management and future research.

A relatively common homozygous TRAPPC4 splicing variant is associated with an early-infantile neurodegenerative syndrome. - Ghosh, Shereen G; Scala, Marcello; Beetz, Christian; Helman, Guy; Stanley, Valentina; Yang, Xiaoxu; Breuss, Martin W; Mazaheri, Neda; Selim, Laila; Hadipour, Fatemeh; Pais, Lynn; Stutterd, Chloe A; et al. (Eur J Hum Genet, 2021)
Trafficking protein particle (TRAPP) complexes, which include the TRAPPC4 protein, regulate membrane trafficking between lipid organelles in a process termed vesicular tethering. TRAPPC4 was recently implicated in a recessive neurodevelopmental condition in four unrelated families due to a shared c.454+3A>G splice variant. Here, we report 23 patients from 17 independent families with an early-infantile-onset neurodegenerative presentation, where we also identified the homozygous variant hg38:11:119020256 A>G (NM_016146.5:c.454+3A>G) in TRAPPC4 through exome or genome sequencing. No other clinically relevant TRAPPC4 variants were identified among any of over 10,000 patients with neurodevelopmental conditions. We found the carrier frequency of TRAPPC4 c.454+3A>G was 2.4-5.4 per 10,000 healthy individuals. Affected individuals with the homozygous TRAPPC4 c.454+3A>G variant showed profound psychomotor delay, developmental regression, early-onset epilepsy, microcephaly and progressive spastic tetraplegia. Based upon RNA sequencing, the variant resulted in partial exon 3 skipping and generation of an aberrant transcript owing to use of a downstream cryptic splice donor site, predicting a premature stop codon and nonsense mediated decay. These data confirm the pathogenicity of the TRAPPC4 c.454+3A>G variant, and refine the clinical presentation of TRAPPC4-related encephalopathy.

Missed diagnoses: Clinically relevant lessons learned through medical mysteries solved by the Undiagnosed Diseases Network. - Cope, Heidi; Spillmann, Rebecca; Rosenfeld, Jill A; Brokamp, Elly; Signer, Rebecca; Schoch, Kelly; Kelley, Emily G; Sullivan, Jennifer A; Macnamara, Ellen; Lincoln, Sharyn; Golden-Grant, Katie; Orengo, James P; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Resources within the Undiagnosed Diseases Network (UDN), such as genome sequencing (GS) and model organisms aid in diagnosis and identification of new disease genes, but are currently difficult to access by clinical providers. While these resources do contribute to diagnoses in many cases, they are not always necessary to reach diagnostic resolution. The UDN experience has been that participants can also receive diagnoses through the thoughtful and customized application of approaches and resources that are readily available in clinical settings. METHODS: The UDN Genetic Counseling and Testing Working Group collected case vignettes that illustrated how clinically available methods resulted in diagnoses. The case vignettes were classified into three themes; phenotypic considerations, selection of genetic testing, and evaluating exome/GS variants and data. RESULTS: We present 12 participants that illustrate how clinical practices such as phenotype-driven genomic investigations, consideration of variable expressivity, selecting the relevant tissue of interest for testing, utilizing updated testing platforms, and recognition of alternate transcript nomenclature resulted in diagnoses. CONCLUSION: These examples demonstrate that when a diagnosis is elusive, an iterative patient-specific approach utilizing assessment options available to clinical providers may solve a portion of cases. However, this does require increased provider time commitment, a particular challenge in the current practice of genomics.
Keywords: Adolescent; Child; Child, Preschool; Databases, Factual; Diagnosis, Computer-Assisted; Female; Genetic Diseases, Inborn; Genetic Testing; Humans; Information Dissemination; Male; Middle Aged; Missed Diagnosis; National Institutes of Health (U.S.); Phenotype; Precision Medicine; Undiagnosed Diseases; United States; Young Adult

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.

Loss of tubulin deglutamylase CCP1 causes infantile-onset neurodegeneration. - Shashi, Vandana; Magiera, Maria M; Klein, Dennis; Zaki, Maha; Schoch, Kelly; Rudnik-Schöneborn, Sabine; Norman, Andrew; Lopes Abath Neto, Osorio; Dusl, Marina; Yuan, Xidi; Bartesaghi, Luca; De Marco, Patrizia; et al. (EMBO J, 2018)
A set of glutamylases and deglutamylases controls levels of tubulin polyglutamylation, a prominent post-translational modification of neuronal microtubules. Defective tubulin polyglutamylation was first linked to neurodegeneration in the () mouse, which lacks deglutamylase CCP1, displays massive cerebellar atrophy, and accumulates abnormally glutamylated tubulin in degenerating neurons. We found biallelic rare and damaging variants in the gene encoding CCP1 in 13 individuals with infantile-onset neurodegeneration and confirmed the absence of functional CCP1 along with dysregulated tubulin polyglutamylation. The human disease mainly affected the cerebellum, spinal motor neurons, and peripheral nerves. We also demonstrate previously unrecognized peripheral nerve and spinal motor neuron degeneration in mice, which thus recapitulated key features of the human disease. Our findings link human neurodegeneration to tubulin polyglutamylation, entailing this post-translational modification as a potential target for drug development for neurodegenerative disorders.

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

De novo mutations in NALCN cause a syndrome characterized by congenital contractures of the limbs and face, hypotonia, and developmental delay. - Chong, Jessica X; McMillin, Margaret J; Shively, Kathryn M; Beck, Anita E; Marvin, Colby T; Armenteros, Jose R; Buckingham, Kati J; Nkinsi, Naomi T; Boyle, Evan A; Berry, Margaret N; Bocian, Maureen; Foulds, Nicola; et al. (Am J Hum Genet, 2015)
Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; this is a unique condition that we now refer to as CLIFAHDD syndrome. Exome sequencing identified missense mutations in the sodium leak channel, non-selective (NALCN) in four families affected by CLIFAHDD syndrome. We used molecular-inversion probes to screen for NALCN in a cohort of 202 distal arthrogryposis (DA)-affected individuals as well as concurrent exome sequencing of six other DA-affected individuals, thus revealing NALCN mutations in ten additional families with "atypical" forms of DA. All 14 mutations were missense variants predicted to alter amino acid residues in or near the S5 and S6 pore-forming segments of NALCN, highlighting the functional importance of these segments. In vitro functional studies demonstrated that NALCN alterations nearly abolished the expression of wild-type NALCN, suggesting that alterations that cause CLIFAHDD syndrome have a dominant-negative effect. In contrast, homozygosity for mutations in other regions of NALCN has been reported in three families affected by an autosomal-recessive condition characterized mainly by hypotonia and severe intellectual disability. Accordingly, mutations in NALCN can cause either a recessive or dominant condition characterized by varied though overlapping phenotypic features, perhaps based on the type of mutation and affected protein domain(s).
Keywords: Arthrogryposis; Contracture; Craniofacial Dysostosis; Cytoskeletal Proteins; Exome; Extremities; Face; Female; Gene Frequency; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant; Male; Muscle Hypotonia; Mutation, Missense; Sodium Channels